INHIBITION OF CALCIUM OXALATE CRYSTALLIZATION BY AN EXTRACT OF OCIMUM BASILICUM SEEDS: AN IN-VITRO STUDY - RAVINDRAKUMAR K, PATEL; SANDIP B, PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Ocimum basilicum (OB) has been used to treat diverse illnesses which include urinary stone disorder for a reason that historical time in India. We investigated OB seeds for antiurolithic activity. Methods: Calcium oxalate crystallization becomes triggered by the addition of 0.01 M sodium oxalate answers in normal human urine and nucleation was done. Results: OB seeds were discovered to be robust and promising antiurolithiatic agents which are in accordance with its use in traditional medication. Conclusion: An extract of the traditional herb OB has super inhibitory activity on crystalluria and therefore might be useful in dissolving urinary stone; however, in addition, a study in animal fashions of urolithiasis is needed to assess its capability antiurolithiatic interest.